Assessment of mothers’ satisfaction with health care during childbirth in a tertiary-level maternity ward - Adriana Haller; Albert Haller; Dejan Tirić; Vajdana Tomić (Medicinski glasnik, 2021)
Aim: To evaluate satisfaction of mothers who gave birth at term with received hospital care and to find areas for improvement at a tertiary hospital. Methods: A cross-sectional study at the Department of Obstetrics & Gynaecology at the University Clinical Hospital Mostar was conducted by an anonymous survey using a questionnaire designed exclusively for this study. A total of 100 mothers were included in the study. Results: Satisfaction with midwives’ communication and their approach to the women during their stay in the delivery room was rated significantly higher (4.7±0.6) when compared to obstetricians-gynaecologists (4.5±0.8) (p=0.02). Midwives were rated better in providing breastfeeding information (4.5±0.8) than for the speed of arrival after a call bell (average grade 4.2±1.0). Respondents were least satisfied with the hygiene (toilet, shower and rooms) and the quality of food (average grades 3.8±1.1 and 3.9±1.0, respectively). Mothers with previous experience in childbirth at the same hospital rated current stay with a similar level of satisfaction. Conclusion: Good communication skills of medical and non-medical staff are a recommended step to maintain mothers′ childbirth satisfaction, while improvement in quality of nutrition and hygiene should be mandatory.
Keywords: delivery room; health care; hygiene; midwifery; obstetrics